2013
DOI: 10.1177/1753944713479996
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone reduces vascular relaxation by altering cyclic adenosine monophosphate pathway and potassium channel activation in male Sprague Dawley rats fed a high-salt diet

Abstract: Inhibition of potassium channel or adenylyl cyclase activation appears to contribute to the mechanisms by which a high-salt diet increases vascular tone. These effects were counteracted by orchidectomy in male Sprague Dawley rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…The increase in blood pressure in rats fed a high salt diet in this study is consistent with our previous findings [8, 9, 24] and that of others [25]. In this study, myocardial oxygen demand (MOD) was calculated as the rate pressure product (RPP) from the product of the heart rate and the systolic blood pressure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in blood pressure in rats fed a high salt diet in this study is consistent with our previous findings [8, 9, 24] and that of others [25]. In this study, myocardial oxygen demand (MOD) was calculated as the rate pressure product (RPP) from the product of the heart rate and the systolic blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a high salt diet has been shown to increase the left ventricular mass, thicken and stiffen the aorta while thickening and narrowing the resistance arteries such as mesenteric, coronary and renal arteries [5, 6, 7]. We have previously shown that high salt diet thickens and narrows the mesenteric artery by promoting vascular smooth muscle cells hyperplasia and extracellular matrix proteins deposition [8] and that, high salt diet also impairs both endothelium - dependent and independent relaxation response to agonist [9, 10]. Other harmful effects of a high salt diet aside BP elevation include, cardiac and vascular hypertrophy as well as renal dysfunction which, may be independent of the arterial pressure [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a vital ion transport determining membrane potential ( Iwamoto, 2006b ), the Na(+)/Ca(2+) exchanger (NCX) type 1 was reported to increase vascular tone by mediating Ca 2+ entry in arterial smooth muscle cells in response to excess salt intake, which could partly explain the link between dietary salt to salt-dependent hypertension ( Iwamoto et al, 2005 ; Iwamoto, 2006a ). Besides, a HSD could inhibit potassium channels ( Oloyo et al, 2013 ). In addition, recent evidence showed that several transient receptor potential channels (TRP), including TRPV1 and TRPC3, are involved in high-salt intake–induced cardiac hypertrophy by mediating mitochondrial function via regulating mitochondrial calcium uptake ( Lang et al, 2015 ; Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Groups 1 and II contained rats that were sham-operated, groups III and IV contained rats that were bilaterally orchidectomised while groups V and VI contained rats that were given Sustanon ® injection as testosterone replacement post orchidectomy. For orchidectomy, randomly selected rats were anaesthetized with intramuscular 90 mg and 10 mg/kg/body weight of ketamine and xylazine respectively [20], [21], [24], thereafter their 2scorotums were removed surgically under an aseptic condition. Sham-operated rats of groups I and II rats only had their scrotal sacs opened and sutured back as a model of sham orchidectomy [21]; [19].…”
Section: Methodsmentioning
confidence: 99%